Casting the net wider? The transformative potential of integrating human rights into the implementation of the WTO Agreement on Fisheries Subsidies. Issue 3 (13th November 2022) - Switzer, Stephanie; Morgera, Elisa; Webster, Elaine
Abstract: The removal of harmful fisheries subsidies is essential to reverse unsustainable fisheries globally. This goal has now, in part, been met following the World Trade Organization Ministerial Conference in June 2022, which adopted an Agreement on Fisheries Subsidies. There is a vast literature on the trade law issues associated with fisheries subsidies, and much has been written on their detrimental environmental impacts. In this article, we take a different approach. We contextualize the elimination of harmful fisheries subsidies as part of the transformative change needed to reverse biodiversity loss, with the integration of human rights an essential precondition to such transformational processes. We develop a mutually supportive interpretation of international environmental law, international trade law and international human rights law, drawing on insights from regime interaction scholarship, to argue for reliance on human rights in the implementation of the historic agreement on the elimination of certain forms of harmful fisheries subsidies.